The Relationship of Eating Intake to Thick Fat Soccer Athletes (Universitas Negeri Semarang, 2022)
Abstract. 66% athletes have not chosen a variety of foods and consume less water, often consume packaged drinks including sweet tea. The importance of athlete's dietary intake correlates with nutritional status, anthropometric profile, and performance. The percentage of excess fat compared to the recommended value was found in groups of male and female athletes. The fulfillment of energy needs, macronutrients micronutrients, and fluid intake of athletes as a whole is still relatively lacking. The purpose of this study was to look the description of the food intake and fat thickness of soccer athletes; Methods: The design used in this study was cross sectional on U-16, U-17, U-18 soccer athletes with a total of 53 soccer athletes from the PS Sleman Development Center. The sampling technique used is purposive sampling. The research instruments used include a 24-hour recall form, a food photo book, and Bioelectrical Impedance Analysis (BIA) tool. The data analysis technique used statistical software through the Chi-Square test; Results: There is no relationship between intake of energy, protein, fat and carbohydrates in percent body fat; Conclusions: Due to the poor intake of energy, protein, fat and carbohydrates for athletes, nutrition education is needed for athletes as the first step in mentoring athletes. Abstract in Indonesia. 66% atlet belum memilih makanan yang beragam dan kurang mengonsumsi air putih, sering mengonsumsi minuman kemasan termasuk teh manis. Pentingnya asupan makan atlet berkorelasi dengan status gizi, profil antropometri, dan performa. Persen lemak berlebih dibandingkan nilai rekomendasi ditemukan pada kelompok atlet laki-laki maupun perempuan. Pemenuhan kebutuhan energi, zat gizi makro, zat gizi mikro, dan asupan cairan atlet secara keseluruhan masih tergolong kurang. Tujuan dari penelitian ini adalah melihat gambaran asupan makan dan tebal lemak atlet sepak bola. Metode: Desain yang digunakan dalam penelitian ini menggunakan cross sectional pada atlet sepak bola U-16, U-17, dan U-18 dengan jumlah 53 atlet sepak bola PS Sleman Development Center. Teknik sampling yang digunakan secara purposive sampling. Instrumen penelitian yang digunakan meliputi formulir Recall 24 jam, buku foto makanan, dan alat Bioelectrical Impedance Analysis (BIA). Teknik analis data digunakan software statistik melalui uji Chi-Square; Hasil: Tidak ada hubungan antara asupan energi, protein, lemak dan karbohidrat dengan persen lemak tubuh; Kesimpulan: Dikarenakan asupan energi, protein, lemak dan karbohidrat atlet tidak baik, diperlukan edukasi gizi kepada atlet sebagai langkah awal pendampingan atlet.